The Good Old Days of Hisbah in Preserving Food Hygiene and Safety - Ishak, Amal Hayati; Tengku Zawawi, Tengku Nurul Saadah; Syed Abdullah, Sharifah Fadylawaty; Muhamad, Mohd Dani (Environment-Behaviour Proceedings Journal, 2021)
Many writings compliment the golden age of Islam, particularly the hisbah institution, as an effective and responsive mechanism to enjoin good and forbid evil. During those times, the real purpose of hisbah served various aspects. This article explores the mechanisms in preserving food hygiene and safety as applied by hisbah. Employing content analysis of relevant manuals, this article concludes on lessons to be learned from the good old days of hisbah. Among the significant findings is the detailed practices to maintain food hygiene and safety taken by the officials more than 700 years ago, reflecting the civilized nation beyond time. Keywords: food hygiene and safety; hisbah; muhtasib eISSN: 2398-4287 Â© 2021. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v6iSI5.2940